Karakteristik Fisik, Kimia, dan Tingkat Kesukaan Permen Jeli Dengan Variasi Rasio Ekstrak Daun Bidara-Bubur Buah Mangga dan Penambahan Gelatin - Sherlya Wanda; Chatarina Lilis Suryani; Dwiyati Pujimulyani (Journal of Food and Agricultural Technology, 2025)
Jelly candy is a soft, elastic confection widely consumed by people of all ages. The innovation of functional jelly candy in this study involved the incorporation of bidara leaf extract and mango pulp to enrich bioactive compounds with antioxidant potential. A factorial randomized block design was used with two factors: the ratio of bidara leaf extract to mango pulp (60:40, 50:50, and 40:60 v/v) and the addition of gelatin (15, 20, and 25 g). The study aimed to obtain a jelly candy formulation with desirable physical, chemical, and sensory qualities and antioxidant activity. The research stages included preparing bidara leaf extract, mango pulp, and jelly candy, followed by analysis of their physical, chemical, and sensory characteristics. Data were statistically analyzed using SPSS Version 25.0 with Univariate Analysis of Variance, followed by One-Way ANOVA and Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that increasing the ratio of bidara leaf extract to mango pulp and adding gelatin increased hardness, elasticity, color intensity, total phenolics and flavonoids, and decreased moisture content. Total phenolic and flavonoid contents increased with treatment. The best formulation was obtained at a 40:60 ratio and 20 g gelatin, producing 25.13% RSA antioxidant activity, 0.98% ash, and 0.20% reducing sugar, indicating potential as a functional food.